63 BLOCKADE OF CENTRAL MELANOCORTIN SIGNALING PROMOTES ACCUMULATION OF LEAN BODY MASS IN RODENT MODELS OF CHRONIC HEART FAILURE. Issue 1 (1st January 2007) - Bowe, D. D.; Scarlett, J. M.; Batra, A. K.; Steiner, R. A.; Marks, D. L.
Abstract : Cachexia is a frequent complication of chronic illness and infectious disease. This devastating state of malnutrition is brought about by a synergistic combination of a decrease in appetite and an increase in metabolism of fat and lean body mass (LBM). Cardiac cachexia is a frequent complication of chronic heart failure (CHF) and is a determining factor in both the quality of life and eventual mortality in CHF patients. Experimental evidence suggests a role for proinflammatory cytokines in the pathogenesis of cardiac cachexia, but the neuronal systems involved in transducing these signals have not been fully defined. To investigate the potential contribution of the central melanocortin system (CMS) in the transduction of cardiac cachexia, we developed two independent rodent models of CHF and measured the effect of CMS signaling blockade on the ability of these animals to accumulate and maintain LBM. In one model, we induced CHF in male 6- to 8-month-old wild-type (WT) C57BL/6J or MC4-RKO mice by permanent coronary artery ligation (CAL) of the left anterior descending coronary artery and measured their LBM 8 weeks after surgery by DEXA analysis. We found that WT mice receiving sham operations ( n = 30) gained significantly more LBM compared with WT mice that had undergone CAL ( n = 14) (13.0 g ± 1.2 g vs 4.1 g ± 2.9 g; p < .01), whereas there was no difference between MC4-RKO mice that received sham operations ( n = 18) compared with MC4-RKO mice that had received CAL ( n = 8) (14.3 g ± 1.5 g vs 12.7 g ± 2.6 g; p = .6). In another model, we induced CHF in 3- to 4-week-old male Wistar rats via ascending aorta banding. Six weeks post-band, they received central administration of either aCSF or AgRP. The accumulation of LBM over a 2-week treatment period was then measured by DEXA analysis. Sham operated rats showed no difference in the accumulation of LBM between groups that had received aCSF ( n = 4) or AgRP ( n = 5) (11.7 g ± 3.2 g vs 13.6 g ± 2.9 g; p = .7). In contrast, banded rats that received aCSF injections ( n = 4) accumulated significantly less LBM compared with banded rats that received AgRP ( n = 4) (6.7 g ± 2.3 g vs 20.1 g ± 3.7 g; p < .05). In summary, we have observed that blockade of CMS signaling attenuates the pathology associated with CHF and that the CMS may be an important therapeutic target.